Analisis Optimasi Persediaan Bahan Baku dengan Menggunakan Metode Economic Order Quantity pada CV Tenun/ ATBM Rimatex Kabupaten Pemalang. - Andini, Wienda Velly; Slamet, Achmad (Management Analysis Journal, 2016)
Inventories of raw materials on this research used EOQ (Economic Order Quantity) method which purpose to analysis and describe inventories of raw materials rayon thread at CV. Tenun Gayor/ATBM Rimatex which is required to achieve optimum result. This research is a quantitative research. Object this research uses EOQ method coverting, safety stock, reorder point, and total inventory cost. The result that there was an optimum purchasing number using EOQ on the thread in 2014 for about 8.721 Kg with 10-times, the safety stock 918 Kg, the reorder point 1.477,62 Kg, and total inventory cost Rp.32.032.628,36.